Lacto S.A. – caso práctico - Vidal Cueva, Cristian Manuel (2019)
In this profesional sufficiency work, the recovery of Company Lacto S.A. will be carried out, with the purpose of comparing the value to be sold commercially against what should be worth if the cash flows brought to present value are considered; this will allow for future trading with interested investors for immediate sale. Do not consider in a sale the value of the money over time, could show an undervalued Company. Macroeconomic factors such as the national and international context for analyzing the outlook for economic activity, variables such as inflation rate, market risk, exchange rate developments, country risk, strategies used by the Company, relevant public information and news, were necessary source in the elaboration of assumptions, which provided the basis for a projection of future events that could affect the Company's cash flows. Accounting aspects, such as the financial situation in which the Company is currently located, the application of the International Financial Reporting Standards (IFRS) as of 2019, such as IFRS 15 in income, IFRS 9 in the Financial Reporting Policy impairment loss estimate, and IAS 41 in the acquisition of the livestock company, will help us to have a more accurate valuation. Considering the sustainability of Lacto S.A. (under the accounting principle company in progress) two different scenarios were developed using the discounted flow model, concluding that, to date, the value of the company in a normal scenario expected ascends to S/. 662 556 and in a pessimistic scenario at S/. 343 709. Similarly, the value of the stock is S/. 6.8 and S/. 2.75 respectively. This result is due to the company's sustained growth with a strengthening and growth of its assets and sales, in addition to the increase in demand in the domestic market.